HAPALINE (ARACEAE: ANGIOSPERM) OF BORNEO - Meekiong, Kalu; Mohd Effendi, Wasli; Hafsah, Nahrawi; Zinnirah, Shabdin (UNIMAS Publisher, 2023)
Tribe Caladieae comprises several genera, Scaphispatha, Caladium, Jasarum, Xanthosoma, Chlorospatha, Syngonium, and Hapaline. Hapaline is a genus of seven published species occurring from Myanmar to China (Yunnan) and south to western Sarawak. All species so far discovered are diminutive to moderate-sized, slender, tuberous or stoloniferous, clump-forming, terrestrial and seasonally dormant or (rarely) evergreen herbs (Boyce, 1996).